Effect of Cilostazol in Preventing Restenosis after Carotid Artery Stenting Using the Carotid Wallstent: A Multicenter Retrospective Study - Takayama, K.; Taoka, T.; Nakagawa, H.; Myouchin, K.; Wada, T.; Sakamoto, M.; Furuichi, K.; Iwasaki, S.; Kurokawa, S.; Kichikawa, K. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Restenosis after CAS is a postoperative problem, with a reported frequency of approximately 2%–8%. However differences in stent design, procedure, and the antiplatelet agent appear to affect the incidence of restenosis. We assessed the frequency of restenosis and the effect of the antiplatelet agent CLZ in preventing restenosis after CAS by the standard procedure using the CWS. MATERIALS AND METHODS: Between May 2010 and October 2011, 62 lesions in 60 consecutive patients underwent CAS using the CWS at 4 medical institutions, and all patients were followed clinically and assessed by sonography, 3D-CTA, or angiography at 3 and 6 months postoperatively. Restenosis was defined as ≥50% stenosis. The incidence of restenosis and the variation in the incidence of restenosis by the difference in type of antiplatelet agent between the CLZ group (n = 30; aspirin, 100 mg, and CLZ, 200 mg) and the non-CLZ group (n = 32; aspirin, 100 mg, and clopidogrel, 75 mg [n = 29]; or ticlopidine, 100 mg [n = 2] or 200 mg [n = 1]) were retrospectively investigated. Two antiplatelet agents were given starting 1 week preoperatively until at least 3 months postoperatively. RESULTS: Restenosis occurred in 5 patients (8.3%), but all were cases of asymptomatic lesions in the follow-up period. All 5 patients with restenosis were in the non-CLZ group, with no cases of restenosis in the CLZ group; the difference was significant (P = .0239). CONCLUSIONS: The restenosis rate after CAS by using the CWS was 8.3%. CLZ was associated with significant inhibition of restenosis. CAScarotid artery stentingCEAcarotid endarterectomyCLZcilostazolCWSCarotid WallstentEPCendothelial precursor cellEPDembolic protection devicePTApercutaneous balloon angioplasty